REPRESENTASI BUDAYA MINUM KOPI DALAM GAME VISUAL NOVEL COFFEE TALK - latifah safarina; Hafiz Aziz Ahmad (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
Games are a form of design that is growing along with the development of design and technology. Games as part of mass media are able to represent a value or point of view, shape understanding by building, conveying and repeating various meaning constructions. The visual novel game Coffee Talk developed by Indonesian game developer Toge Productions, shapes and represents the phenomenon of coffee drinking culture as the main narrative. Coming at the right time along with the development of this culture both in the world and Indonesia itself. Therefore, this research will explain the representation of the phenomenon of coffee drinking culture formed in Coffee Talk game. The research method used in this research is a qualitative method with descriptive analysis. It is conducted to produce an in-depth understanding about elements used in the representation. The results of the research reveal that the Coffee Talk game is able to represent the phenomenon of coffee drinking culture well, through narrative, gameplay, character, visual background, background music (bgm) and game atmosphere formed based on reality.